2018
DOI: 10.1007/s40097-018-0271-8
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis, characterization, and antibacterial activity of zinc oxide nanoparticles derived from Bauhinia tomentosa leaf extract

Abstract: A facile, eco-friendly synthesis of zinc oxide nanoparticles (ZnO NPs) employing Bauhinia tomentosa leaf extract as bioreducing agent was reported. The green-synthesized ZnO NPs were characterized by UV-Vis, TEM, EDX, XRD, and FTIR analyses. The formation of ZnO NPs was confirmed by the appearance of characteristic SPR peak at 370 nm due to the collective oscillation of electrons in the conduction band in UV-Vis spectra. The hexagonal morphology exhibiting nanosized ZnO was observed from the TEM and XRD analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(51 citation statements)
references
References 28 publications
13
38
0
Order By: Relevance
“…The XRD spectrum line extension of diffraction peaks is an indication of the nano-meter range of the synthesized products, moreover, the diffraction peaks from other metal species was absent suggesting the synthesized ZnO nanoparticles are free from any other impurities. Similar results of the XRD analysis of ZnO nanoparticles synthesized by using biological material are in close agreement with multiple studies (Azizi et al, 2014;Nazir et al, 2018;Sharmila et al, 2018).…”
Section: Xrd Analysissupporting
confidence: 91%
“…The XRD spectrum line extension of diffraction peaks is an indication of the nano-meter range of the synthesized products, moreover, the diffraction peaks from other metal species was absent suggesting the synthesized ZnO nanoparticles are free from any other impurities. Similar results of the XRD analysis of ZnO nanoparticles synthesized by using biological material are in close agreement with multiple studies (Azizi et al, 2014;Nazir et al, 2018;Sharmila et al, 2018).…”
Section: Xrd Analysissupporting
confidence: 91%
“…The aqueous extract of Bauhinia tomentosa leaves and 0.01 M FeCl 3 solution were combined to effectuate the synthesis of iron (II) oxide nanoparticles. The extract was prepared by soaking the leaves in distilled water for 24 h 22 . The freshly prepared 0.01 M FeCl 3 solution was added dropwise to the leaf extract in a 1:1 ratio with continuous stirring.…”
Section: Methodsmentioning
confidence: 99%
“…According to Pratap et al, ZnO synthesized by using green route Coriandrum sativum leaf extract exhibit antibacterial activity at concentration more than 100 mg/ml [59] . Sharmila et al, demonstrated antibacterial activity of ZnO nanoparticles (22–93 nm) synthesized through green route Bauhinia tomentosa leaf extract, which showed antibacterial activity against Gram positive and Gram negative bacteria [60] . Several reports suggest that the action of ZnO on bacterial species is due to release of reactive oxygen species (ROS) species and zinc ions.…”
Section: Resultsmentioning
confidence: 99%